Effect of Precursors on Flavonoid Production in Pegaga Cell Suspension Cultures - Tan, Suat Hian; Maziah, Mahmood (2013)
The present study aimed to investigate the effect of precursors on flavonoid production in cell of the elite C. asiatica accession UPM03. The effect of phenylalanine and tyrosine on enhancing the flavonoid production were examined. The results obtained showed that the intracellular flavonoid content increased by a 11.5-fold and 3.2-fold with the feeding of 60mg/L phenyalanine and 40mg/L tyrosine, respectively. The addition of 60mg/L phenylalanine and 40mg/L tyrosine have successfully produced increased amount of flavonoid in the cell.